1999
DOI: 10.2307/1370064
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Associations of Migrating and Overwintering Grassland Birds in Southern Texas

Abstract: Abstract.We report on the habitat associations of 21 species of grassland birds overwintering in or migrating through southern Texas, during 1991-1992 and 1992-1993. Ninety percent of our grassland bird observations were made during winter and spring, and only 10% occurred during fall. Grassland species made up a high proportion of the total bird densities in grassland and shrub-grassland habitats, but much lower proportions in the habitats with more woody vegetation. Fewer grassland species were observed in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 20 publications
0
38
1
Order By: Relevance
“…This pattern has been well documented for grassland birds (Coppedge et al 2001;Cunningham and Johnson 2006;Winter et al 2006;Block and Morrison 2010), but has also been observed for mammals (Krogh et al 2002;Blaum et al 2007a) and reptiles (Mendelson and Jennings 1992;Pike et al 2011). When woody cover exceeds species-specific thresholds, which as yet have been poorly established, populations of grassland-associated species are displaced (Grant et al 2004;Sirami et al 2009) and animal communities shift from being dominated by grassland-associated species to shrubland-associated species (Igl and Ballard 1999;Rosenstock and Van Riper 2001;Skowno and Bond 2003;Sirami and Monadjem 2012). Overall, richness of animal communities is likely maximized where cover of woody plants is below the threshold levels that displace grassland specialists but above levels where habitat becomes more exclusively suitable for shrub-associated species (Fig.…”
Section: Animalsmentioning
confidence: 71%
“…This pattern has been well documented for grassland birds (Coppedge et al 2001;Cunningham and Johnson 2006;Winter et al 2006;Block and Morrison 2010), but has also been observed for mammals (Krogh et al 2002;Blaum et al 2007a) and reptiles (Mendelson and Jennings 1992;Pike et al 2011). When woody cover exceeds species-specific thresholds, which as yet have been poorly established, populations of grassland-associated species are displaced (Grant et al 2004;Sirami et al 2009) and animal communities shift from being dominated by grassland-associated species to shrubland-associated species (Igl and Ballard 1999;Rosenstock and Van Riper 2001;Skowno and Bond 2003;Sirami and Monadjem 2012). Overall, richness of animal communities is likely maximized where cover of woody plants is below the threshold levels that displace grassland specialists but above levels where habitat becomes more exclusively suitable for shrub-associated species (Fig.…”
Section: Animalsmentioning
confidence: 71%
“…Transects were randomly placed within patches using ArcGIS 10.0 (ESRI 2011) but constrained so that transects were .150 m apart and .100 m from patch edges to ensure independence between sites and prevent any double counting. Sampling was conducted during daylight hours by one observer on days with winds less than 20 km/h and no precipitation (Igl and Ballard 1999). Surveys were conducted four v www.esajournals.org times in 2011 and 2013 and three times in 2012.…”
Section: Data Collectionmentioning
confidence: 99%
“…Although the complexity of avian life cycles complicates conservation and management efforts, the extent and duration of seasonal movements by grassland birds emphasizes the need for information in areas other than the breeding grounds (Igl and Ballard 1999). Monitoring avian communities during winter is challenging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such emphasis on breeding season ecology occurs despite the fact that most grassland species are migratory and spend at least half the year in migration and on separate wintering grounds (Igl and Ballard 1999). As a result, it is still uncertain what role habitat loss or alteration on the wintering grounds of grassland birds may play in their recent decline.…”
Section: Introduction: Grassland Birds and Natural Resource Extractionmentioning
confidence: 99%